TELAAH FAKTOR KEPUTUSAN ORANG TUA DALAM PEMILIHAN SEKOLAH DASAR DI KOTA PURWAKARTA - Rayi Siti Fitriani; Yudi Bachtiar; Ihsan Rizali; Hany Handayani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
Choosing a school is one of the efforts parents make to provide education for their children's lives. The choice of school is certainly based on motivations that become factors to consider in the decision-making process. The location and environment of the school; the school's vision and mission; the curriculum; the profile of the teachers; facilities; the school's achievements; costs, understanding of children, and parents' expectations are factors of both internal and external motivation that determine the choice of school. This research uses a survey method to examine the dominant factors that influence 156 parents, who are respondents in this study, in choosing schools located in the Purwakarta district.